High-thermal-conductivity plastic and preparation method thereof

Through the synergistic effect of modified carbon nanotubes and nanosilver and aluminum nitride, combined with the modification of hydrophobic longan chains and epoxy stearic acid, the problem of insufficient thermal conductivity of high-density polyethylene is solved and high-density polyethylene is achieved The excellent thermal conductivity and mechanical properties of ethylene plastics are improved.

CN119119617AInactive Publication Date: 2024-12-13JIESHOU MINGTAI PLASTIC IND TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411481952.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The thermal conductivity of high-density polyethylene is low, resulting in insufficient heat dissipation of products. The existing aluminum nitride application in plastics is limited by insufficient hydrolysis and dispersion performance, so it is impossible to build an effective thermal conductivity network.

Method used

By modifying the acid-treated carbon nanotubes with aluminum nitride, grafting nanosilver, and modifying aluminum nitride with hydrophobic longan chains and epoxy stearic acid, a modified thermal conductivity filler was prepared, combined with high density Polyethylene plastic forms a three-dimensional thermal conductivity network to improve thermal conductivity and hydrolysis resistance.

Benefits of technology

It significantly improves the thermal conductivity and mechanical properties of high-density polyethylene plastics, forms a uniformly dispersed thermal conductivity network, enhances the interface compatibility between the thermal filler and the matrix, reduces the interface thermal resistance effect, and improves the hydrophobic properties of aluminum nitride and Dispersive performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005097640280000081
    Figure BDA0005097640280000081
Patent Text Reader

Abstract

The invention discloses a high thermal conductive plastic and a preparation method thereof, and belongs to the technical field of high polymer material preparation, the high thermal conductive plastic comprises the following raw materials by weight: 100-110 parts of high density polyethylene, 8-14 parts of a modified thermal conductive filler, 0.02-0.2 part of an antifoaming agent, 0.5-1 part of a plasticizer, and 2-4 parts of an anti-aging agent. According to the invention, the high-density polyethylene plastic is taken as a matrix, and the modified heat-conducting filler with good dispersing performance and heat-conducting performance is introduced, so that the heat-conducting performance of the prepared plastic is improved, and the high-density polyethylene plastic is endowed with excellent mechanical performance; the long alkyl chain with hydrophobic performance is grafted on the surface of the aluminum nitride, so that the hydrophobic performance of the modified aluminum nitride is effectively improved, the surface energy of the modified aluminum nitride is reduced, the modified aluminum nitride is endowed with good hydrolysis resistance, and meanwhile, the dispersing performance of the modified aluminum nitride is also improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer material preparation, and in particular relates to a high thermal conductivity plastic and a preparation method thereof. Background Art

[0002] High-density polyethylene is a synthetic thermoplastic resin with good chemical stability, water resistance and toughness. It is widely used as a polymer in aerospace, electronics, and industrial fields. However, high-density polyethylene has low thermal conductivity, with a thermal conductivity of only 0.4-0.5W / mK at room temperature, resulting in the inability of products produced from it to dissipate heat in a timely manner. This not only reduces the service life of high-density polyethylene products, but also poses a safety hazard to people's lives and property.

[0003] In the prior art, aluminum nitride is usually added as a thermally conductive filler when preparing thermally conductive plastics. Aluminum nitride is an artificially synthesized covalent bond compound belonging to the hexagonal crystal system and has excellent thermal conductivity. It can conduct heat through phonons, reduce scattering, and improve thermal conductivity efficiency. However, due to the presence of aluminum ions in the molecular structure of aluminum nitride, aluminum nitride is prone to hydrolysis, which limits the application of aluminum nitride in improving the thermal conductivity of plastics. In addition, aluminum nitride has a high surface energy and is prone to agglomeration in organic matter, and its thermal conductivity cannot be fully exerted. In addition, introducing only a single aluminum nitride as a thermally conductive filler for plastics cannot construct an effective thermal conductive network. Therefore, how to effectively improve the hydrolysis resistance of aluminum nitride and its dispersion performance in plastic groups, and on this basis construct an effective thermal conductive network, is a technical problem that needs to be solved at present. Summary of the invention

[0004] The object of the present invention is to provide a high thermal conductivity plastic and a preparation method thereof to solve the problems in the background technology.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A high thermal conductivity plastic, comprising the following raw materials in parts by weight:

[0007] 100-110 parts of high-density polyethylene plastic, 8-14 parts of modified thermal conductive filler, 0.02-0.2 parts of defoamer, 0.5-1 parts of plasticizer, 2-4 parts of anti-aging agent;

[0008] The modified thermally conductive filler is prepared by the following steps:

[0009] A1. Add acid-treated carbon nanotubes to N,N-dimethylformamide, disperse by ultrasonic, add triethylenetetramine in a nitrogen atmosphere, stir and react at room temperature for 22-24 hours, wash and dry, place in anhydrous ethanol, add modified aluminum nitride, mix evenly, add 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride, stir and react in an ice-water bath for 12-18 hours, filter, wash with deionized water, and dry to obtain modified carbon nanotubes; use N,N-dimethylformamide as solvent, react triethylenetetramine with carboxyl groups on the surface of the acid-treated carbon nanotubes to obtain amino carbon nanotubes, and then use 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride as a catalyst, react the amino carbon nanotubes with the modified aluminum nitride containing carboxyl groups on the surface, and graft the modified aluminum nitride onto the carbon nanotubes;

[0010] A2. Add modified carbon nanotubes to N,N-dimethylformamide, disperse by ultrasonic, add silver nitrate aqueous solution dropwise at 65-70°C while stirring, control the dropping time to be 3-8min, continue to stir and react at room temperature for 2-3h after the dropping is completed, let stand for 3-5h, filter, wash and dry to obtain a modified thermal conductive filler; using N,N-dimethylformamide as solvent and reducing agent, the remaining amino and carboxyl groups on the modified carbon nanotubes can be complexed with silver ions, and under the reducing action of N,N-dimethylacetamide, a modified thermal conductive filler with surface loaded nanosilver and aluminum nitride is obtained.

[0011] Furthermore, the dosage ratio of the N,N-dimethylformamide, acid-treated carbon nanotubes, triethylenetetramine, anhydrous ethanol, modified aluminum nitride and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride is 150 mL: 10-14 g: 0.5-5 mL: 100 mL: 6-8 g: 3-8 g.

[0012] Furthermore, the dosage ratio of the N,N-dimethylformamide, the modified carbon nanotubes and the silver nitrate aqueous solution is 200 mL: 10-14 g: 20 mL; and the concentration of the silver nitrate aqueous solution is 10.4-16.2 mg / mL.

[0013] Furthermore, the acid-treated carbon nanotubes are obtained by stirring and reacting single-walled carbon nanotubes in a mixed acid solution at 60° C. for 4 hours.

[0014] Furthermore, the dosage ratio of the single-walled carbon nanotubes to the mixed acid solution is 11-15 g:100 mL; the mixed acid solution is composed of 98 wt% concentrated sulfuric acid and 68 wt% nitric acid mixed in a volume ratio of 2-3:1.

[0015] Furthermore, the modified aluminum nitride is prepared by the following steps:

[0016] Add epoxy stearic acid to anhydrous ethanol, stir to mix, add aluminum nitride and Tween 80, mix evenly, stir to react at 55-60°C for 2-3h, filter, wash with anhydrous ethanol, and dry to obtain modified aluminum nitride; use Tween 80 as a surfactant and epoxy stearic acid as a hydrophobic modification agent to graft epoxy stearic acid on the surface of aluminum nitride through a ring-opening reaction to obtain hydrolysis-resistant modified aluminum nitride.

[0017] Furthermore, the usage ratio of anhydrous ethanol, epoxy stearic acid, aluminum nitride and Tween 80 is 100 mL: 0.5-3 g: 7-9 g: 0.2-1 mL.

[0018] A method for preparing a high thermal conductivity plastic comprises the following steps:

[0019] Step S1: Mixing of raw materials

[0020] Add high-density polyethylene plastic, modified thermal conductive filler, defoamer, plasticizer and anti-aging agent into a mixer and mix evenly to obtain a mixture;

[0021] Step S2: Processing of the mixture

[0022] The mixed material is added into an extruder for melt extrusion, and after cooling, pelletizing and drying, a high thermal conductive plastic is obtained.

[0023] Beneficial effects of the present invention:

[0024] The surface of the modified thermal conductive filler of the present invention contains a long hydrophobic alkane chain. When blended with high-density polyethylene plastic, the modified thermal conductive filler can be uniformly dispersed in the high-density polyethylene matrix, and the interface compatibility between the modified thermal conductive filler and the high-density polyethylene plastic is enhanced, the interface thermal resistance effect generated between the modified thermal conductive filler and the matrix is ​​effectively reduced, and the thermal conductivity of the plastic is improved. In addition, the modified aluminum nitride and nano-silver loaded on the surface of the modified thermal conductive filler can play a "bridge" role between adjacent modified thermal conductive fillers, which is conducive to the adjacent modified thermal conductive fillers forming a three-dimensional thermal conductive network in the plastic matrix. When the surface temperature of the high-density polyethylene plastic is high, the single-walled carbon nanotubes in the modified thermal conductive filler can form a heat conduction path inside the plastic matrix. Compared with multi-walled carbon nanotubes, the interlayer thermal resistance of the single-walled carbon nanotubes is smaller, so that heat is quickly transferred to the surroundings, and under the action of the heat conductive medium of the modified aluminum nitride and nano-silver particles, the heat is transferred to the air and dissipated, giving the high-density polyethylene plastic excellent thermal conductivity.

[0025] The invention uses high-density polyethylene plastic as a matrix, and introduces a modified thermally conductive filler with good dispersibility and thermal conductivity, thereby not only improving the thermal conductivity of the prepared plastic, but also giving the high-density polyethylene plastic excellent mechanical properties. At the same time, the invention uses epoxy stearic acid to modify the surface of aluminum nitride, and grafts a long alkyl chain with hydrophobic properties on the surface of aluminum nitride, thereby effectively improving the hydrophobicity of the modified aluminum nitride, reducing the surface energy of the modified aluminum nitride, giving the modified aluminum nitride good hydrolysis resistance, and also improving the dispersibility of the modified aluminum nitride. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Example 1

[0028] This embodiment provides a modified thermally conductive filler, which is prepared by the following steps:

[0029] A1. Add 11 g of single-walled carbon nanotubes to 100 mL of a mixed acid solution of 98 wt % concentrated sulfuric acid and 68 wt % nitric acid in a volume ratio of 2:1, stir and mix, and react at 60° C. for 4 h to obtain acid-treated carbon nanotubes.

[0030] A2, add 10g of acid-treated carbon nanotubes to 150mL of N,N-dimethylformamide, ultrasonically disperse, add 0.5mL of triethylenetetramine in a nitrogen atmosphere, stir and react at room temperature for 22h, then wash and dry, place in 100mL of anhydrous ethanol, add 6g of modified aluminum nitride, mix well, add 3g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, stir and react in an ice-water bath for 12h, filter, wash with deionized water, and dry to obtain modified carbon nanotubes;

[0031] A3. Add 10 g of modified carbon nanotubes to 200 mL of N,N-dimethylformamide, disperse by ultrasonic, and dropwise add 18 mL of 10.4 mg / mL silver nitrate aqueous solution at 65 °C while stirring. The dropping time is controlled to be 3 min. After the dropping is completed, continue to stir and react at room temperature for 2 h. After standing for 3 h, filter, wash and dry to obtain a modified thermally conductive filler.

[0032] Example 2

[0033] This embodiment provides a modified thermally conductive filler, which is prepared by the following steps:

[0034] A1. Add 13 g of single-walled carbon nanotubes to 100 mL of a mixed acid solution of 98 wt % concentrated sulfuric acid and 68 wt % nitric acid in a volume ratio of 2.5:1, stir and mix, and react at 60° C. for 4 h to obtain acid-treated carbon nanotubes;

[0035] A2, add 12g of acid-treated carbon nanotubes to 150mL of N,N-dimethylformamide, ultrasonically disperse, add 2mL of triethylenetetramine in a nitrogen atmosphere, stir and react at room temperature for 23h, then wash and dry, place in 100mL of anhydrous ethanol, add 7g of modified aluminum nitride, mix well, add 5g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, stir and react in an ice-water bath for 15h, filter, wash with deionized water, and dry to obtain modified carbon nanotubes;

[0036] A3. Add 12 g of modified carbon nanotubes to 200 mL of N,N-dimethylformamide, disperse by ultrasonic, and dropwise add 22 mL of 13.2 mg / mL silver nitrate aqueous solution at 63 °C while stirring. The dropping time is controlled to be 5 min. After the dropping is completed, continue to stir and react at room temperature for 2.5 h. After standing for 4 h, filter, wash and dry to obtain a modified thermally conductive filler.

[0037] Example 3

[0038] This embodiment provides a modified thermally conductive filler, which is prepared by the following steps:

[0039] A1. Add 15 g of single-walled carbon nanotubes to 100 mL of a mixed acid solution of 98 wt % concentrated sulfuric acid and 68 wt % nitric acid in a volume ratio of 3:1, stir and mix, and react at 60° C. for 4 h to obtain acid-treated carbon nanotubes.

[0040] A2, add 14g of acid-treated carbon nanotubes to 150mL of N,N-dimethylformamide, ultrasonically disperse, add 5mL of triethylenetetramine in a nitrogen atmosphere, stir and react at room temperature for 24h, wash and dry, place in 100mL of anhydrous ethanol, add 8g of modified aluminum nitride, mix well, add 8g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, stir and react in an ice-water bath for 18h, filter, wash with deionized water, and dry to obtain modified carbon nanotubes;

[0041] A3. Add 14 g of modified carbon nanotubes to 200 mL of N,N-dimethylformamide, disperse by ultrasonic, and dropwise add 26 mL of 16.2 mg / mL silver nitrate aqueous solution at 70°C while stirring. The dropping time is controlled to be 8 min. After the dropping is completed, continue to stir the reaction at room temperature for 3 h. After standing for 5 h, filter, wash and dry to obtain a modified thermally conductive filler.

[0042] Example 4

[0043] This embodiment provides a modified aluminum nitride, which is prepared by the following steps:

[0044] Add 0.5 g of epoxy stearic acid to 100 mL of anhydrous ethanol, stir to mix, add 7 g of aluminum nitride and 0.2 mL of Tween 80, mix evenly, stir to react at 55° C. for 2 h, and then filter, wash with anhydrous ethanol, and dry to obtain modified aluminum nitride.

[0045] Example 5

[0046] This embodiment provides a modified aluminum nitride, which is prepared by the following steps:

[0047] Add 2.5 g of epoxy stearic acid to 100 mL of anhydrous ethanol, stir to mix, add 8 g of aluminum nitride and 0.6 mL of Tween 80, mix evenly, stir to react at 58° C. for 2.5 h, and then filter, wash with anhydrous ethanol, and dry to obtain modified aluminum nitride.

[0048] Example 6

[0049] This embodiment provides a modified aluminum nitride, which is prepared by the following steps:

[0050] Add 3 g of epoxy stearic acid to 100 mL of anhydrous ethanol, stir to mix, add 9 g of aluminum nitride and 1 mL of Tween 80, mix evenly, stir to react at 60° C. for 3 h, and then filter, wash with anhydrous ethanol, and dry to obtain modified aluminum nitride.

[0051] Example 7

[0052] This embodiment provides a method for preparing a high thermal conductivity plastic, comprising the following steps:

[0053] Step S1: Mixing of raw materials

[0054] 100 parts by weight of high-density polyethylene plastic, 8 parts by weight of modified thermal conductive filler, 0.02 parts by weight of defoamer, 0.5 parts by weight of plasticizer and 2 parts by weight of anti-aging agent are added into a mixer and mixed evenly to obtain a mixture;

[0055] Step S2: Processing of the mixture

[0056] The mixed material is added into an extruder for melt extrusion, and after cooling, pelletizing and drying, a high thermal conductive plastic is obtained.

[0057] Example 8

[0058] This embodiment provides a method for preparing a high thermal conductivity plastic, comprising the following steps:

[0059] Step S1: Mixing of raw materials

[0060] 105 parts by weight of high-density polyethylene plastic, 11 parts by weight of modified thermal conductive filler, 0.1 parts by weight of defoamer, 0.8 parts by weight of plasticizer and 3 parts by weight of anti-aging agent are added into a mixer and mixed evenly to obtain a mixture;

[0061] Step S2: Processing of the mixture

[0062] The mixed material is added into an extruder for melt extrusion, and after cooling, pelletizing and drying, a high thermal conductive plastic is obtained.

[0063] Example 9

[0064] This embodiment provides a method for preparing a high thermal conductivity plastic, comprising the following steps:

[0065] Step S1: Mixing of raw materials

[0066] 110 parts by weight of high-density polyethylene plastic, 14 parts by weight of modified thermal conductive filler, 0.2 parts by weight of defoamer, 1 part by weight of plasticizer and 4 parts by weight of anti-aging agent are added into a mixer and mixed evenly to obtain a mixture;

[0067] Step S2: Processing of the mixed material: The mixed material is added into an extruder for melt extrusion, and after cooling, pelletizing and drying, a high thermal conductive plastic is obtained.

[0068] Comparative Example 1: Compared with Example 7, the modified thermal conductive filler is replaced with carbon nanotubes in equal amount, and the rest is the same.

[0069] Comparative Example 2: Compared with Example 7, the modified thermal conductive filler is replaced with aluminum nitride in equal amount, and the rest is the same.

[0070] Comparative Example 3: Compared with Example 7, the modified thermal conductive filler is replaced with nanosilver in equal amount, and the rest is the same.

[0071] Performance tests were performed on Examples 7 to 9 and Comparative Examples 1 to 3. Thermal conductivity test: thermal conductivity: refer to GB / T 22588-2008, impact resistance: refer to GB / T 1043-2008, tensile strength: refer to GB / T 1040-2006. The results are shown in Table 1:

[0072] Table 1

[0073]

[0074] It can be seen from Table 1 that the thermal conductivity of the plastics prepared from the modified thermally conductive filler in Examples 7-9 is significantly higher than that of the plastics prepared from Comparative Examples 1-3, and has good thermal conductivity, and the impact strength and tensile strength are both greater than those of Comparative Examples 1-3, and has good mechanical properties; in addition, compared with Comparative Examples 2-3, Example 7 has a higher thermal conductivity, indicating that the modified thermally conductive filler prepared from modified aluminum nitride and nanosilver particles in cooperation with single-walled carbon nanotubes has better thermal conductivity for preparing plastics.

[0075] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0076] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high thermal conductivity plastic, characterized in that: It includes the following raw materials in parts by weight: 100-110 parts of high-density polyethylene plastic, 8-14 parts of modified thermal conductive filler, 0.02-0.2 parts of defoamer, 0.5-1 parts of plasticizer, 2-4 parts of anti-aging agent; The modified thermally conductive filler is prepared by the following steps: A1. Add acid-treated carbon nanotubes to N,N-dimethylformamide, disperse by ultrasonication, add triethylenetetramine in a nitrogen atmosphere, and react with stirring at room temperature for 22-24 hours, then wash and dry, place in anhydrous ethanol, add modified aluminum nitride, mix well, add 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, react with stirring for 12-18 hours in an ice-water bath, filter, wash with deionized water, and dry to obtain modified carbon nanotubes; A2. Add modified carbon nanotubes to N,N-dimethylformamide, disperse by ultrasonic, add silver nitrate aqueous solution dropwise while stirring at 65-70°C, control the dropping time to be 3-8min, after the dropping is completed, continue to stir the reaction at room temperature for 2-3h, let it stand for 3-5h, then filter, wash and dry to obtain the modified thermal conductive filler.

2. A high thermal conductivity plastic according to claim 1, characterized in that: The dosage ratio of the N,N-dimethylformamide, acid-treated carbon nanotubes, triethylenetetramine, anhydrous ethanol, modified aluminum nitride and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride is 150 mL: 10-14 g: 0.5-5 mL: 100 mL: 6-8 g: 3-8 g.

3. The high thermal conductivity plastic according to claim 1, characterized in that: The acid-treated carbon nanotubes are single-walled carbon nanotubes obtained by stirring and reacting in a mixed acid solution at 60° C. for 4 hours.

4. A high thermal conductivity plastic according to claim 3, characterized in that: The dosage ratio of the single-walled carbon nanotubes to the mixed acid solution is 11-15 g:100 mL; the mixed acid solution is composed of 98 wt% concentrated sulfuric acid and 68 wt% nitric acid mixed in a volume ratio of 2-3:

1.

5. The high thermal conductivity plastic according to claim 1, characterized in that: The modified aluminum nitride is prepared by the following steps: Add epoxy stearic acid to anhydrous ethanol, stir and mix, add aluminum nitride and Tween 80, mix evenly, stir and react at 55-60° C. for 2-3 hours, filter, wash with anhydrous ethanol, and dry to obtain modified aluminum nitride.

6. A high thermal conductivity plastic according to claim 5, characterized in that: The usage ratio of the anhydrous ethanol, epoxy stearic acid, aluminum nitride and Tween 80 is 100 mL: 0.5-3 g: 7-9 g: 0.2-1 mL.

7. The high thermal conductivity plastic according to claim 1, characterized in that: The dosage ratio of the N,N-dimethylformamide, the modified carbon nanotubes and the silver nitrate aqueous solution is 200 mL: 10-14 g: 20 mL; the concentration of the silver nitrate aqueous solution is 10.4-16.2 mg / mL.

8. The method for preparing a high thermal conductivity plastic according to claim 1, characterized in that: The following steps are involved: Step S1: Mixing of raw materials Add high-density polyethylene plastic, modified thermal conductive filler, defoamer, plasticizer and anti-aging agent into a mixer and mix evenly to obtain a mixture; Step S2: Processing of the mixture The mixed material is added into an extruder for melt extrusion, and after cooling, pelletizing and drying, a high thermal conductive plastic is obtained.